Analysis of tumor-infiltrating NK and T cells highlights IL-15 stimulation and TIGIT blockade as a combination immunotherapy strategy for soft tissue sarcomas. Issue 2 (6th November 2020) - Judge, Sean J; Darrow, Morgan A; Thorpe, Steve W; Gingrich, Alicia A; O'Donnell, Edmond F; Bellini, Alyssa R; Sturgill, Ian R; Vick, Logan V; Dunai, Cordelia; Stoffel, Kevin M; Lyu, Yue; Chen, Shuai; et al.
Abstract : Purpose: Given the unmet need for novel immunotherapy in soft tissue sarcoma (STS), we sought to characterize the phenotype and function of intratumoral natural killer (NK) and T cells to identify novel strategies to augment tumor-infiltrating lymphocyte (TIL) function. Experimental design: Using prospectively collected specimens from dogs and humans with sarcomas, archived specimens, and The Cancer Genome Atlas (TCGA) data, we evaluated blood and tumor NK and T cell phenotype and function and correlated those with outcome. We then assessed the effects of interleukin 15 (IL-15) stimulation on both NK and T cell activation and TIGIT upregulation. Finally, we evaluated cytotoxic effects of IL-15 combined with TIGIT blockade using a novel anti-TIGIT antibody. Results: TILs were strongly associated with survival outcome in both archived tissue and TCGA, but higher TIL content was also associated with higher TIGIT expression. Compared with blood, intratumoral NK and T cells showed significantly higher expression of both activation and exhaustion markers, in particular TIGIT. Ex vivo stimulation of blood and tumor NK and T cells from patients with STS with IL-15 further increased both activation and exhaustion markers, including TIGIT. Dogs with metastatic osteosarcoma receiving inhaled IL-15 also exhibited upregulation of activation markers and TIGIT. Ex vivo, combined IL-15 and TIGIT blockade using STS blood and tumor specimens significantly increased cytotoxicity against STS targets. Conclusion: Intratumoral NK and T cells are prognostic in STS, but their activation is marked by significant upregulation of TIGIT. Our data suggest that combined IL-15 and TIGIT blockade may be a promising clinical strategy in STS.